Vyākaraṇasiddhāntasudhānidhih - Viśveśvara, 18th cent (Caukhambā-Saṃskrta-granthamālā ;, 1914)
Commentary on Patañjalī's Vyākaraṇamahābhāṣya, ch. 1-3, in turn, a commentary on Pāṇini's Aṣṭādhyāyī, basic work of Sanskrit grammar; includes the text of the Aṣṭādhyāyī, ch. 1-3.